Towards rigorously faking bidirectional model transformations - POSKITT, Christopher M. (Institutional Knowledge at Singapore Management University, 2014)
Bidirectional model transformations (bx) are mechanisms for automatically restoring consistency between multiple concurrently modified models. They are, however, challenging to implement; many model transformation languages not supporting them at all. In this paper, we propose an approach for automatically obtaining the consistency guarantees of bx without the complexities of a bx language. First, we show how to "fake" true bidirectionality using pairs of unidirectional transformations and inter-model consistency constraints in Epsilon. Then, we propose to automatically verify that these transformations are consistency preserving – thus indistinguishable from true bx – by defining translations to graph rewrite rules and nested conditions, and leveraging recent proof calculi for graph transformation verification.